China’s “Belt and Road Initiative” in Sri Lanka : Debt Diplomacy in Hambantota Port Investment - Adhe Nuansa Wibisono (Mandala: Jurnal Ilmu Hubungan Internasional, 2019)
This article will discuss the impact of China's debt diplomacy in Sri Lanka through the Belt Road Initiative (BRI) which has an impact on China's control of the Hambantota Port for 99 years. The Belt and Road Initiative with the promotion of infrastructure investment is an example of the use of Chinese soft power diplomacy on a global level. In the Hambantota Port development project, Sri Lanka relied on development funding from China and subsequently defaulted. At first the Sri Lankan Government under the leadership of Mahinda Rajapaksa opened the investment door for China. From 2010 to 2015, China provided a $ 4.8 billion loan to build various infrastructure projects including the Hambantota Port, new airports, power plants and highways. Sri Lanka was then caught up in debt diplomacy carried out by China. Then, this article also discusses the response and efforts of the Sri Lankan government to renegotiate the ownership of Chinese shares in the Hambantota Port project. The Sri Lankan government is working hard to get out of the debt diplomacy trap. This article also then discusses the strategic economic and political impacts of controlling the Hambantota Port by China. This article uses books, research reports, theses, journals, newspapers, and online news as reference material.